Implementation Of The Keyword Mnemonic Method And Its Effectiveness To Improve Arabic Vocabulary Mastery - Ferdinand, Ilham; Yasry, Fajar Alpy (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to determine: 1. Arabic vocabulary mastery of MTs Plus Darul Hufaz Jatinangor students before implementing the mnemonic method, 2. Arabic vocabulary mastery of MTs Plus Darul Hufaz Jatinangor students before implementing the mnemonic method, 3. The effectiveness of implementing the mnemonic method with keywords on mastery Arabic Vocabulary Students MTs Plus Darul Hufaz Jatinangor. This research is experimental, using a quasi-experimental design model. This study has two variables, and the first is the independent variable, namely keyword mnemonics, and the second dependent variable is Arabic vocabulary mastery. The population of this study was all students of class VII MTs Plus Darul Hufadz Sumedang. Then a sample of class VII B was selected as the experimental class and VII A as the control class. The data collection technique is by giving a pretest, pretest, and posttest as a test. The data analysis technique uses the "t" test with the help of SPSS, which previously carried out the analysis prerequisite test. The results of this study are the results obtained from these calculations is the value of Sig. (2-tailed) of 0.000. Sig results. (2-tailed) of 0.000, which means that this value is smaller than 0.05, which can be concluded that Ha is accepted and Ho is rejected.